Wrist-worn accelerometry for runners: Objective quantification of training load - Stiles, V. H.; Pearche, M.; Moore, I. S.; lanford, J.; Rowlands, A. V. (Medicine & Science in Sports & Exercise, 2018)
Purpose This study aimed to apply open-source analysis code to raw habitual physical activity data from wrist-worn monitors to: 1) objectively, unobtrusively, and accurately discriminate between "running" and "nonrunning" days; and 2) develop and compare simple accelerometer-derived metrics of external training load with existing self-report measures.